Community awareness and use of anti-Mullerian hormone (AMH) testing in Australia: Presenter(s): Tessa Copp, The University of Sydney, Australia. (April 2023) - Thompson, Rachel; Hammarberg, Karin; Doust, Jenny; Lensen, Sarah; Peate, Michelle; Lieberman, Devora; Mol, Ben; McCaffery, Kirsten
Abstract : Background: The anti-Mullerian Hormone (AMH) test is a blood test indicating the number of eggs left in a woman's ovaries. Whilst the test is helpful in assisted reproduction, studies have found the test cannot reliably predict the likelihood of pregnancy or timing of menopause. It is unclear what people in Australia know about the AMH test or how widely it is being used, particularly for women without infertility. Method: Data were collected via an online or telephone survey of a probability-based population panel in January 2022. All females aged 18-55 years were invited to participate. Questions about AMH testing included if and how participants had heard about AMH testing, whether they had ever had an AMH test, the main reason for AMH testing, and how they accessed the test. Findings: 1773 of the 2423 women who were invited responded. Of these, 229 participants (13%) had heard about AMH testing and 124 had had an AMH test 7%). Having had the test was associated with age and educational attainment. The highest rate of testing was for those aged 35-39 (14%), followed by 10% for those aged 40-44 years. 51% of women had the test during infertility investigations, 19% because they were considering pregnancy, 9% because they were curious, 11% to find out if a medical condition had affected their fertility, 5% as they were considering egg freezing, and 2% because they were considering delaying pregnancy. Discussion: Whilst a substantial proportion of women underwent AMH testing for reasons supported by evidence, many did not. Potential implications of AMH testing in scenarios not related to infertility investigation include a false sense of security about delaying pregnancy, unwarranted anxiety about not being able to conceive, pressure to conceive earlier than desired or unnecessary procedures.